2007
DOI: 10.1111/j.1537-2995.2007.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

AABB survey of transfusion‐related acute lung injury policies and practices in the United States

Abstract: There is wide variability in procedures and policies related to the diagnosis of and donor investigation and/or management of TRALI cases. Lack of a consensus approach may partly reflect limitations in understanding of TRALI pathogenesis. The survey suggests that increased education of transfusion medicine practitioners is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…An AABB survey of member institutions conducted in 2006 demonstrated the variability in practices at blood centers and hospitals, highlighting the disparate criteria used to initiate a TRALI investigation and the various donor management decisions in different clinical scenarios [14]. Many institutions reported used the Canadian Consensus Conference definition of TRALI, but often modified it, in ways that were not qualified in the survey.…”
Section: Current Blood Center Practices For Donor Deferralmentioning
confidence: 98%
See 2 more Smart Citations
“…An AABB survey of member institutions conducted in 2006 demonstrated the variability in practices at blood centers and hospitals, highlighting the disparate criteria used to initiate a TRALI investigation and the various donor management decisions in different clinical scenarios [14]. Many institutions reported used the Canadian Consensus Conference definition of TRALI, but often modified it, in ways that were not qualified in the survey.…”
Section: Current Blood Center Practices For Donor Deferralmentioning
confidence: 98%
“…Not surprisingly, blood centers and transfusion services have implemented different policies and procedures to address the standard [13][14][15]. An AABB survey of member institutions conducted in 2006 demonstrated the variability in practices at blood centers and hospitals, highlighting the disparate criteria used to initiate a TRALI investigation and the various donor management decisions in different clinical scenarios [14].…”
Section: Current Blood Center Practices For Donor Deferralmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de las limitaciones metodológicas de este tipo de estudios, es un método que ayuda a dar un panorama general de la práctica clínica, por lo que ha sido utilizado con frecuencia en diferentes países con el objetivo específico de describir la utilización de hemoderivados en diferentes contextos clínicos; su empleo en las UCI ha sido escaso [8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Introducción «Lo Que Sabemos Lo Sabemos Juntos» Hans Sigaarunclassified
“…An AABB international survey 16 conducted in 2006 indicated that if an implicated donor was found to carry an antibody directed toward an antigen in the recipient, 79% of respondents would defer donation for all blood components from that individual and 14% would defer donation of plasma and platelets only. If a donor was identified as carrying an antibody with no recipient type available, 43% of respondents would defer donation from that individual.…”
Section: Prevention Of Tralimentioning
confidence: 99%